2001
DOI: 10.1097/00006454-200101000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of mother-to-infant transmission of hepatitis C virus

Abstract: Our prospective study showed that the transmission rate of mother-to-infant HCV infection was 7.8% in anti-HCV antibody-positive mothers. Risk was related to the presence of maternal HCV viremia at delivery and a high viral load in the mothers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
49
0
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(58 citation statements)
references
References 25 publications
5
49
0
3
Order By: Relevance
“…On the other hand, LFTs are not necessarily predictive of the clinical course of HCV, since liver biopsy might reveal advanced disease even if LFTs are normal or only slightly elevated [20]. In accordance with other studies [25,28], the course of LFTs and viral load in the six cases presented here, suggests that even small children are capable of exhibiting a vigorous HCV-driven inflammatory response. Four of these children had maximal LFT values up to sevenfold of the normal value in the first year of life.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…On the other hand, LFTs are not necessarily predictive of the clinical course of HCV, since liver biopsy might reveal advanced disease even if LFTs are normal or only slightly elevated [20]. In accordance with other studies [25,28], the course of LFTs and viral load in the six cases presented here, suggests that even small children are capable of exhibiting a vigorous HCV-driven inflammatory response. Four of these children had maximal LFT values up to sevenfold of the normal value in the first year of life.…”
Section: Discussionsupporting
confidence: 84%
“…Four of these children had maximal LFT values up to sevenfold of the normal value in the first year of life. In line with the description of the natural course of vertical infection by Tajiri et al [28], maximal LFT levels were followed by a decline of HCV viral load and a normalization of LFTs. In this context, Resti et al [25] observed a range of ALT abnormalities in the first year of life among 62 patients and concluded that high LFTs at onset might be associated with an increased chance of viral clearance.…”
Section: Discussionsupporting
confidence: 73%
“…HCV-RNA (cp/ml) À 10 infection, maternal viral load is believed to play an important role in the HCV transmission to the newborn [Lin et al, 1994[Lin et al, , 1995Ohto et al, 1994;Spencer et al, 1997;Tajiri et al, 2001]. In this survey, the mean viral titre of mothers having infected their child was higher as compared to that of non-transmitting: while the difference did not reach statistical significance, it showed a trend.…”
Section: Discussionmentioning
confidence: 61%
“…Although most studies have reported transmission of HCV to infants only from mothers who had detectable HCV-RNA (31,(34)(35)(36)(37), a large multicenter study has reported 5 infections in infants from mothers who had only HCV antibodies (38). This may be due to fluctuating viremia that is undetectable at the time of testing.…”
Section: Mother-to-infant Transmission For Hcvmentioning
confidence: 99%